The marketing effectiveness of Tabung Haji`s Link Card (THLC) among rural account holders in Sabah / Mohamad Harith Annuar - Annuar, Mohamad Harith (2016)
This research is an attempt to investigate the marketing effectiveness of Tabung Haji Link Card among rural account holders in Sabah. Over 300 questionnaires were distributed during the study. The researcher identified that there are three (3) independent variables involved in this study namely Location, Advertising, and Product. In the findings, it is shown that Product has a perfectly positive significant relationship with the dependent variable. The dependent variable in this study is the marketing effectiveness of THLC among rural account holders in Sabah. Respondent involved in this study are among account holders who are registered under Lembaga Tabung Haji.